Intercomparison of Magnitudes and Trends in Anthropogenic Surface Emissions From Bottom‐Up Inventories, Top‐Down Estimates, and Emission Scenarios. Issue 8 (13th August 2020) - Elguindi, N.; Granier, C.; Stavrakou, T.; Darras, S.; Bauwens, M.; Cao, H.; Chen, C.; Denier van der Gon, H. A. C.; Dubovik, O.; Fu, T. M.; Henze, D. K.; Jiang, Z.; et al.
Abstract: This study compares recent CO, NO x, NMVOC, SO2, BC, and OC anthropogenic emissions from several state‐of‐the‐art top‐down estimates to global and regional bottom‐up inventories and projections from five Shared Socioeconomic Pathways (SSPs) in several regions. Results show that top‐down emissions derived in several recent studies exhibit similar uncertainty as bottom‐up inventories in some regions for certain species and even less in the case of Chinese CO emissions. In general, the largest discrepancies are found outside of regions such as the United States, Europe, and Japan where the most accurate and detailed information on emissions is available. In some regions such as China, which has recently undergone dynamical economic growth and changes in air quality regulations, the top‐down estimates better capture recent emission trends than global bottom‐up inventories. These results show the potential of top‐down estimates to complement bottom‐up inventories and to aide in the development of emission scenarios, particularly in regions where global inventories lack the necessary up‐to‐date and accurate information regarding regional activity data and emission factors such as Africa and India. Areas of future work aimed at quantifying and reducing uncertainty are also highlighted. A regional comparison of recent CO and NO x trends in the five SSPs indicate that SSP126, a strong pollution control scenario, best represents the trends from the top‐down and regional bottom‐up inventories in the United States, Europe, and China, while SSP460, a low‐pollution control scenario, lies closest to actual trends in West Africa. This analysis can be useful for air quality forecasting and near‐future pollution control/mitigation policy studies. Key Points: Top‐down emissions from several recent studies are within the range of bottom‐up inventories and exhibit a similar level of uncertainty for some regions and species In China, the United States, and Europe emission trends in the last decade from SSP126 match most closely actual trends from bottom‐up and top‐down estimates In Western Africa and India recent emission trends from low pollution control scenarios (SSP460 and SSP370, respectively) match most closely actual trends